Exploring Internal Market Potential for Business Unit Development: Evidence from UIN Sayyid Ali Rahmatullah Tulungagung - Umam, Syamsul (Jurnal At-Tamwil: Kajian Ekonomi Syariah, 2026)
Purpose – The purpose of this paper is to describe and explore the results of a market potential survey by mapping respondent profiles to initiate the development of a campus business unit that focuses on providing daily goods and services for the academic community of UIN SATU. Design/Methods/Approach – This study employed a quantitative approach using a survey method. A questionnaire survey was administered to the academic community of UIN SATU. The questionnaire comprised several groups of questions aimed at exploring the respondents' demographic and their consumption behavior related to campus-based goods and services. Findings – The findings reveal a structurally consistent and necessity-driven consumption pattern across the academic community. Essential categories, particularly Food & Beverages, Health-related products, and Academic Supplies, consistently record the highest index values. Although segment-based variations in magnitude are observed, especially among Premium respondents, the overall ranking structure remains stable across gender, faculty, and engagement groups. Research Implications/Limitations – This study provides an empirical foundation for data-driven campus business planning by demonstrating the usefulness of descriptive index analysis in profiling institutional consumption patterns. However, the analysis relies on descriptive analysis only. Future studies should employ probabilistic designs and explanatory models to deepen strategic insights. Originality/Value – This study offers an integrated index-based profiling of campus consumption behavior by linking demographic, faculty, and engagement segments to BLU-oriented business development strategy in higher education institutions.